Spatial Spillovers in Emerging Market Spreads - Dell'Erba, Salvatore (IMF Working Papers; Working Paper, 2011)
We use novel spatial econometrics techniques to explore spillovers in the sovereign bond market for 24 emerging economies during 1995-2010. The paper extends the previous literature focusing on spillover effects from advanced to emerging economies by analyzing transmission of shocks across emerging markets. After controlling for the impact of global factors, we find strong evidence of spillovers from both sovereign spreads and macroeconomic fundamentals in neighboring emerging economies. In addition to the geographical proximity, the channels of spatial transmission include trade and financial linkages. The results of the paper highlight the importance of accounting not only for spillovers from advanced economies to emerging markets, but also across emerging markets when analyzing sovereign spreads.